05.25: Lateral torsional buckling investigation on welded Q460GJ structural steel unrestrained singly‐symmetric beams under a point load. (13th September 2017) - Zhang, Yue; Yang, Bo; Xiong, Gang; Elchalakani, Mohamed; Nie, Shidong
ABSTRACT: This paper reports the results of experimental tests and parametric analyses for the lateral torsional buckling (LTB) strengths of welded singly‐symmetric I‐shaped cross‐section beams fabricated from Q460GJ structural steel plates. Simply supported beams with varying lengths and sectional dimensions were tested by using a special testing system. In order to achieve the ideal loading condition and the simply supported boundary condition, a special testing system including the and the loading system and supporting system was invented and used in the experimental tests, and the testing system was verified. Meanwhile, a finite element model established by a finite element program ABAQUS, correlated well with the experimental result, was used to conduct the parametric studies. The result showed that the finite element model can be useful in simulation. Thus, the parametric studies were conducted, using the verified finite element model, to investigate the effect of member slenderness and height‐to‐width ratio. It is well known that each design specification has its own background and compiling principles, and the formula of each design code is very difficult. Q460GJ structural steel is a new material, thus, it is very hard to say which design code is more suitable to predict the lateral torsional buckling strengths of welded H‐shaped sectional beams fabricated from Q460GJ structural steel plates. While comparing the test results and the parametric studies results with the prediction of some design code including Chinese design code GB50017‐201X (2012) and GB50017‐2003 (2003), American code (ANSI/AISC360‐10, 2010) and EC3 (2005), some important conclusions can be found. The results demonstrate that the global stability design methods in GB50017‐201X (2012) and EC3 (2005) for rolled sections or equivalent welded sections may be more appropriate for Q460GJ structural steel beams. In addition, the design methods in GB50017‐2003 (2003) and the American code (ANSI/AISC360‐10, 2010) may not be conservative for Q460GJ structural steel beams.